Cooperative Learning and Social Capital Formation in ‎Multicultural Social Studies Classrooms: Putnam’s Framework ‎for Trust, Reciprocity, and Adolescent Democratic ‎Participation - Ilham Syah; Indah Ainun Mutiara; Romdah Romansyah; Sangputri Sidik (JPI: Jurnal Pustaka Indonesia, 2026)
This paper develops a conceptual framework for how cooperative learning in ‎multicultural Social Studies (IPS) classrooms might foster Putnamian social ‎capital intergroup trust, civic reciprocity, and democratic participation among ‎adolescent students in heterogeneous schools. Rather than reporting findings ‎from an original survey or focus-group study, the analysis synthesizes Robert ‎Putnam's (1993, 2000) social capital framework with the cooperative-learning ‎literature (Johnson & Johnson, 2009) to derive a set of theoretically grounded ‎propositions linking specific dimensions of cooperative learning quality to specific ‎dimensions of social capital formation, and to the moderating role of classroom ‎heterogeneity. The framework proposes that cooperative learning quality is ‎associated with social capital formation, with intergroup trust expected, on ‎contact-theory grounds, to be the most foundational dimension, followed by civic ‎reciprocity and democratic participation. Classroom heterogeneity is proposed to ‎moderate the cooperative-learning-to-trust pathway, such that the trust-building ‎function of cooperative structures is amplified when diversity is structurally ‎embedded in task design. Three candidate mechanisms role rotation, accountable ‎interdependence, and deliberative dialogue are proposed as the processes ‎through which cooperative structures might translate into Putnamian social ‎capital. The paper offers this model as a heuristic for future empirical research, ‎together with a set of testable propositions rather than confirmed findings, with ‎implications for IPS curriculum development and teacher training in pluralistic ‎educational contexts‎.‎